#TITLE_ALTERNATIVE# - ARIYANTO KOEHUAN (NIM : 231 04 022); Pembimbing : Dr. Ir. Priyono Sutikno, VERDY
The environmental impact of burning fossil fuels and their inevitable depletion have led to a growing interest in renewable energy sources such as wind energy. Wind energy is a low density source of power, available almost everywhere but not necessarily all the time, and its efficient exploitation requires continue inÃ‚Â–depth studies. To make wind power economically feasible, it is important to maximize the efficiency of converting wind energy into mechanical energy. Progress of aerodynamics of wind turbine has ensured the new concept design turbines such as a stall controlled machine. Of all the different aspects involved in this process, rotor aerodynamics is a key determinant for achieving this goal. As the use of large scale commercial wind turbines is expanded over the world, the wind turbine industry is facing many difficulties in consulting efficient wind turbine machine, which is caused by the inability to adequately predict structural loading and power output. A design method with refer to calculation constructively by using an algorithm of FORTRAN programming language and conducted simulation by using CFD or Fluent program have been developed, so that the expense and time needed in optimum aerodynamic design of a wind turbine blade can be minimized. This designed method use wind turbine aerodynamic theory, namely BEM (blade element momentum) was applied in an algorithm of FORTRAN programming language. In this simulation, by using Fluent version 6.1, two and three dimension models were used. Simulation by two dimension model was conducted to obtain the characteristics of airfoils were used along span (profile of airfoils were s816, s817 and s818). Three dimension model simulation aim to obtain phenomenon of wake rotation of stream flow around rotor blade. Simulation model used is relative velocity formulation model or multiple reference frames model (MRF) with model of viscous flow k - & for the incompressible flow field. Design and analysis of wind turbine rotor by using the FORTRAN program and also simulation with Fluent gave acceptable result. The results show that the speed at blade tip is 62,3 m/s by FORTRAN or 64 m/s by Fluent at 12 m/s wind speed (with calculation difference of 1,02 %). Whereas thrusts force that occurred at rotor turbine was calculated as 50920,47 N with FORTRAN or 51444,663 N with Fluent at 12 m/s wind speed (calculation difference 2,6 %). By using a whole rotor with 10o pre-cone it was found that the rotor with 100 pre-cone more optimal than rotor without pre-cone, although level of output power for rotor without precone bigger than rotor with 10o pre-cone.